2018
DOI: 10.1093/schbul/sby012
|View full text |Cite
|
Sign up to set email alerts
|

Models of Schizotypy: The Importance of Conceptual Clarity

Abstract: The observation of psychosis-like traits that resemble symptoms of schizophrenia and bipolar disorder, both among healthy relatives of psychotic patients and among the general population, can be traced to the early 20th century.1,2 These traits have since been described within various models of illness and health (ie, normal/abnormal personality, abnormal psychotic continua), each giving rise to concepts such as "schizotypy," "psychoticism," and "psychosis-proneness" that are not necessarily interchangeable, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
1
3

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 141 publications
(131 citation statements)
references
References 61 publications
(66 reference statements)
2
115
1
3
Order By: Relevance
“…Some theories of relations between personality and psychotic disorders hypothesized a latent discontinuity, with risk of psychosis limited to a qualitatively distinct subgroup 43,104 . Studies of this question produced mixed results, and further research is needed to determine whether any discontinuities exist in the psychosis superspectrum 105,106 .…”
Section: Structural Evidencementioning
confidence: 99%
“…Some theories of relations between personality and psychotic disorders hypothesized a latent discontinuity, with risk of psychosis limited to a qualitatively distinct subgroup 43,104 . Studies of this question produced mixed results, and further research is needed to determine whether any discontinuities exist in the psychosis superspectrum 105,106 .…”
Section: Structural Evidencementioning
confidence: 99%
“…Enhanced quantitative approaches may further refine what we consider to be psychosis risk, and will ideally involve several methods and measures, multiple genetic risk metrics, and careful attention to psychometrics within each population being measured. [47][48][49][50] Limitations One limitation of this study is a reliance on questionnaire rather than interview data.…”
Section: Discussionmentioning
confidence: 99%
“…In order to enroll individuals prone to report PLEs, the scores on the questionnaire were evaluated, and those who had intermediate to high levels of positive schizotypy were considered to take part in the experience sampling study. Thus, we selected those participants who scored at least 4 on the unusual experiences (UE) subscale of the short Oxford‐Liverpool Inventory of Feelings and Experiences (sO‐LIFE) as eligible for the study.…”
Section: Methodsmentioning
confidence: 99%
“…In order to investigate the bidirectional link between subjective sleep quality and daytime PLEs, we conducted a 3‐week long experience sampling study. A non‐clinical sample of young adults showing moderate to high levels of positive schizotypy (which reflects proneness to PLEs ) participated in the study. It has been shown that PLEs show subtle daily fluctuations , but the temporal associations between sleep quality, negative affect and psychotic‐like phenomena so far have not been examined among healthy adults showing moderate to high levels of positive schizotypy.…”
Section: Introductionmentioning
confidence: 99%